Review Regarding the Influence of Cryogenic Milling on Materials Used in the Aerospace Industry - Bogdan Nita; Raluca Ioana Tampu; Catalin Tampu; Bogdan Alexandru Chirita; Eugen Herghelegiu; Carol Schnakovszky (Journal of Manufacturing and Materials Processing)
In the aerospace industry, an important number of machined parts are submitted for high-performance requirements regarding surface integrity. Key components are made of materials selected for their unique properties and they are obtained by milling processes. In most situations, the milling process uses cooling methods because, in their absence, the material surface could be affected by the generated heat (temperatures could reach up to 850 °C), the residual stress, the cutting forces, and other factors that can lead to bad integrity. Cryogenic cooling has emerged as a pivotal technology in the manufacturing of aeronautical materials, offering enhanced properties and efficiency in the production process. By utilizing extremely low temperatures, typically involving liquid nitrogen or carbon dioxide, cryogenic cooling can significantly enhance the material’s properties and machining processes. Cryogenic gases are tasteless, odorless, colorless, and nontoxic, and they evaporate without affecting the workers’ health or producing residues. Thus, cryogenic cooling is also considered an environmentally friendly method. This paper presents the advantages of cryogenic cooling compared with the classic cooling systems used industrially. Improvements in terms of surface finishing, tool life, and cutting force are highlighted.